2016
DOI: 10.1115/1.4033018
|View full text |Cite
|
Sign up to set email alerts
|

Robust Control of Uncertain Nonlinear Systems: A Nonlinear DOBC Approach

Abstract: This paper advocates disturbance observer based control (DOBC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In the proposed eventtriggering mechanism, the control signal is transmitted via communication network only when a predetermined lower threshold that depending on the control signal has been reached. Moreover, without the ISS assumption depending on the measurement errors, the nonlinear disturbance observer-based control (DOBC) approach [24][25][26][27] is applied to effectively estimate the total disturbance. By the proposed disturbance observerbased event-triggered control method, it is shown that the global boundedness of the signals in closed-loop system is guaranteed, and the tracking error is ensured to converge to a set, which can be made as small as desired by adjusting control parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In the proposed eventtriggering mechanism, the control signal is transmitted via communication network only when a predetermined lower threshold that depending on the control signal has been reached. Moreover, without the ISS assumption depending on the measurement errors, the nonlinear disturbance observer-based control (DOBC) approach [24][25][26][27] is applied to effectively estimate the total disturbance. By the proposed disturbance observerbased event-triggered control method, it is shown that the global boundedness of the signals in closed-loop system is guaranteed, and the tracking error is ensured to converge to a set, which can be made as small as desired by adjusting control parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, robust control is mostly achieved at a price of sacrificing the nominal control performance since the control performance in the nominal case is usually not directly taken into account [15]. Such a design philosophy may cause unsatisfactory overall performance since most practical systems usually operate around their nominal operation point, and rarely operate far away from their nominal operation point [5].…”
Section: Introductionmentioning
confidence: 99%
“…The nominal dynamics of the uncertain nonlinear systems under consideration are nonlinear, which differs from [17], [18], [19]. A preliminary result of this paper has been published in [5], which provides a simple local result. However, to surmount the limitation of local result, it is quite challenging to conduct stability analysis as it is hard to evaluate the bounds of coupling terms between the system dynamics and the estimator error dynamics outside a local region.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many advanced control approaches have been employed to handle disturbance attenuation and rejection problem, such as adaptive dynamical compensation [4], control [5], output regulator theory [6], and so on. In late 1980s, disturbance‐observer‐based control (DOBC) theory was studied and the basic idea of the DOBC scheme is to employ the observer to estimate the effects of external disturbances on the system and compensate in the feedforward channel [7–9]. However, in most of the DOBC results, the external system modelling interference is considered as harmonic disturbance or constant disturbance of linear system.…”
Section: Introductionmentioning
confidence: 99%